Aplikasi Perhitungan Faktor Koreksi Kalibrasi Berbasis Android di Dinas Tenaga Kerja dan Transmigrasi - Azegap, Syahrul; Akbar, Lalu Ahmad Syamsul Irfan (Depertment of Electrical Engineering University of Mataram, 2024)
This study focuses on developing an Android-based application to simplify the calculation of calibration correction factors for measuring instruments, specifically aiding the Department of Manpower and Transmigration in ensuring the accuracy of equipment used for workplace safety. The application addresses the limitations of manual calculations and suboptimal software by providing a user-friendly interface for inputting calibration data, automatically computing correction factors, and storing calculation histories. The development process includes planning, designing, algorithm implementation in Kotlin, application development in Android Studio, and comprehensive testing for functionality and usability. The results demonstrate that the application enhances efficiency, accuracy, and consistency in the calibration process, which is vital for maintaining high safety standards. User feedback indicates high satisfaction with the application's ease of use and reliability. Moving forward, the application is expected to make significant contributions to calibration, with ongoing updates to meet evolving user needs, thereby reinforcing the collaboration between educational institutions and industry while promoting quality standards in various sectors.